MODIFIKASI PEMERIKSAAN RADIOGRAFI THORAX PADA PASIEN CORONAVIRUS DISEASE 2019 (COVID-19) - Rindayana Rindayana; Agung Nugroho Setiawan; Siti Daryati; Andrey Nino Kurniawan (Perhimpunan Radiografer Indonesia (PARI), 2022)
Background: Patients with an indication of COVID-19 in the Intensive Care Unit and Emergency Department have special handling because they cannot be examined at the radiology installation, so it is necessary to modify the radiographic procedures. The purpose of this study was to describes the modification of procedures and the quality of the image produced from chest X-ray procedure. Methods: This type of research is a qualitative study with a case study design through the research articles from international journals. Results: The modification of the radiographic proedures of chest X-ray with COVID-19 includes preparation of patients using masks, radiographers using PPE and arranging portable x-rays from outside the patient's room glass to minimize contact with the patient. Between the X-ray source and the patient there is a glass medium as a barrier, and necessary to modify 180 - 300 cm of SID, increases of 22-28% kV and maximum use of 12.5 mili Ampere second. The projection used is Antero Posterior, with patient position semi erect in the patient bed. The image quality from the modification technique is assessed is the aspect of anatomical information, which is visible from the lungs to the costophrenic sinus, good contrast by being able to show between objects, minimizing noise and avoiding artifacts that can be caused by glass, and the exposure index assessment has a higher number than standard techniques due to factors the exposure used is higher. Conclusions: Modifications are needed to ensure the safety aspects of radiographers from infectious diseases and to obtain quality images for diagnosing diseases that are spreading in the world today.